Coal and Energy in South Africa Considering a Just Transition - Marais, Lochner; Burger, Philippe; Malene Campbell; Stuart Paul Denoon-Stevens; Deirdre van Rooyen (Edinburgh University Press, 2021)
Coal and Energy in South Africa: Considering a Just Transition investigates the consequences of shifting social responsibilities, new inequalities and the sustainability concerns created by the likely energy transition in Africa to end the fossil-fuel era. Focusing on the local realities in a growing coal and energy town of South Africa, Emalahleni, it explores whether a just transition from coal-generated energy is possible and what the local implications will be of this global restructuring of the energy sector.